Research funding and economic aspects of the Antarctic krill fishery. (September 2022) - Cappell, Rod; MacFadyen, Graeme; Constable, Andrew
Abstract: The Antarctic krill fishery has increased in recent years to more than two-thirds of an interim catch level of 620, 000 tonnes in the Atlantic Sector, FAO Fishery Area 48. Members of the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) have expressed concern that catches at these levels, if taken from small areas, could impact krill-dependent predators. In recent years, CCAMLR has been unable to agree on small-scale spatial management measures influencing the spatial distribution of krill catch. Some krill-fishing Members contend that more science is needed as CCAMLR is obliged to use the precautionary approach informed by the best available science. The availability of scientific information is dependent on funding and these considerations should be included in decision-making to ensure the costs for the necessary research to manage the fishery will be met. In this article we review the economics of the Antarctic krill fishery, the beneficiaries of the fishery, the costs of producing the scientific information currently available and the extent of current contributions. Based on this analysis, we propose that CCAMLR Scientific Committee designs a research strategy for the krill fishery in which research needs are identified, costed and implemented. This should include a funding mechanism to sustain these research activities and ensure appropriate contributions from those benefiting from the fishery.